Development and Validity Test of Social Attachment Multidimensional Scale - Yang, Maosheng; Suanpong, Kwanrat; Ruangkanjanases, Athapol; Yu, Wei; Xu, Hongyu (Frontiers in Psychology, 2022)
Social attachment can explain well the bond between users and social media, but existing research lacks measures of social attachment scales. To this end, this study takes attachment theory as the basis for scale development. On the basis of the development of multidimensional scales for adult, brand and local attachment, it combines existing relevant studies on social attachment, selects three representative social media such as Tik Tok, WeChat and MicroBlog as theoretical samples, explores the concept and structure of social attachment, and develops a social attachment scale through qualitative interviews and open-ended questionnaires. This study applied SPSS 24.0 and Mplus 7.0 to test the Social Attachment Scale. The findings reveal that social attachment consists of three constructs: social connection, social dependence and social identity, and the scale possesses high reliability and validity. This study has developed and validated a social attachment scale in the context of social software use, realizing a quantitative study of social attachment and providing a basis for future empirical research related to social attachment.